Islamic Jurisprudence Perspective on the Post-Marriage Grave Visiting Tradition in Kou Village, Curio District, Enrekang Regency - Mardiana, Mardiana; Hamzah, Nur Asia; Billah, Muktashim (JURNAL MAHASISWA YUSTISI, 2025)
This study examines the tradition of visiting graves after marriage from the perspective of Islamic jurisprudence, prompted by differing public opinions regarding its legal status and permissibility. The research focuses on two main issues: (1) the practice of post-marriage grave visiting in Kou Village, Curio District, Enrekang Regency; and (2) the Islamic jurisprudential view on this tradition. A qualitative research method was applied, utilizing both primary and secondary data sources. Data collection techniques included interviews, documentation, and literature review from books, journals, and articles. Data were analyzed through reduction, presentation, and verification processes. The findings reveal that: (1) The tradition is considered permissible by the local community, though its practice is optional; some couples observe it while others do not. (2) From an Islamic jurisprudence perspective, grave visiting is generally recommended in Islam as a reminder of death and as a means to pray for the deceased, which extends to the post-marriage grave visiting practice.